Evaluation of a fully automated von Willebrand factor assay panel for the diagnosis of von Willebrand disease. Issue 2 (27th February 2020) - Stufano, Francesca; Baronciani, Luciano; Bucciarelli, Paolo; Boscarino, Marco; Colpani, Paola; Pagliari, Maria Teresa; Peyvandi, Flora
Abstract: Introduction: von Willebrand disease (VWD) diagnosis starts with first level tests: factor VIII coagulant activity, VWF antigen (VWF:Ag) and platelet‐dependent VWF activity (VWF:RCo, VWF:Ab, VWF:GPIbR or VWF:GPIbM). The VWF collagen binding (VWF:CB) assay measures the binding capacity of von Willebrand factor (VWF) to collagen. Aim: To assess, in previously diagnosed VWD patients, the performance of a fully automated chemiluminescent test panel including VWF:Ag, VWF:GPIbR and VWF:CB assays. Methods: The patients, historically evaluated using in‐house VWF:Ag and VWF:CB assays and an automated latex enhanced immunoassay VWF:GPIbR method, were re‐evaluated using the VWF test panel HemosIL AcuStar. Results: The VWF:GPIbR/VWF:Ag and VWF:CB/VWF:Ag obtained by means of AcuStar showed an overall good concordance with the corresponding data obtained at the time of the historical diagnosis. When discrepancies occurred, these were generally due to the lower VWF:CB/VWF:Ag obtained with AcuStar as compared with that obtained with the historical methods and this affected particularly the diagnosis of VWD type 2M. Together, the AcuStar VWF:GPIbR/VWF:Ag and VWF:CB/VWF:Ag were able to distinguish type 1 from types 2A, 2B and 2M, whereas no distinction was possible between type 2A and 2B. Conclusion: The AcuStar panel offers a good performance in the differential diagnosis between VWD type 1 and 2A/2B patients. A high rate of coincidence with historical diagnosis was obtained for VWD types 3, 2A/2B and 1. Even though in some cases more tests (eg, RIPA/multimeric analysis) are needed to complete an accurate VWD classification, the AcuStar panel is considered a sensitive, rapid and reliable tool to diagnose VWD patients.